2013
DOI: 10.1111/tbed.12113
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Distribution of Foot-and-Mouth Disease Virus Serotype A and O in Bangladesh

Abstract: Foot-and-mouth disease (FMD) is endemic in Bangladesh and is predominantly due to FMDV serotype O. In 2012, FMD outbreaks were identified in five different districts of Bangladesh. Of 56 symptomatic cattle epithelial tissue samples, diagnostic PCR assay based on 5'-URT detected 38 FMDV infections. Viral genotyping targeting VP1-encoding region confirmed emergence of two distinct serotypes, A and O with an abundance of serotype A in Chittagong and Gazipur districts and serotype O in Pabna and Faridpur. Only sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 8 publications
3
57
0
1
Order By: Relevance
“…In this study, nucleotide diversities In Asia, including India, Pakistan, Afghanistan and Bangladesh, where type A FMDV is also endemic, this serotype (albeit from the Asia topotype) co-exists with serotypes O and Asia 1 but serotype A is the most divergent and is responsible for most of the recent FMD outbreaks (Jamal et al, 2011a;Jamal et al, 2011b;Mittal et al, 2005;Nandi et al, 2013). In contrast, in Kenya serotypes O, SAT 1 and SAT 2 have caused most of the outbreaks, until the recent 2012 to 2013 upsurge of serotype A outbreaks.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this study, nucleotide diversities In Asia, including India, Pakistan, Afghanistan and Bangladesh, where type A FMDV is also endemic, this serotype (albeit from the Asia topotype) co-exists with serotypes O and Asia 1 but serotype A is the most divergent and is responsible for most of the recent FMD outbreaks (Jamal et al, 2011a;Jamal et al, 2011b;Mittal et al, 2005;Nandi et al, 2013). In contrast, in Kenya serotypes O, SAT 1 and SAT 2 have caused most of the outbreaks, until the recent 2012 to 2013 upsurge of serotype A outbreaks.…”
Section: Discussionmentioning
confidence: 73%
“…circulating FMDVs is required to enable selection of the most appropriate vaccine strain (Bastos et al, 2003;Kitching, 2005), yet this has been seldom undertaken in Kenya. Elsewhere, large numbers of serotype A outbreaks have reported, in recent years, in Asia and the Middle-East (Jamal et al, 2011a;Nandi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The etiological agent, FMD virus (FMDV), is a single-stranded positive-sense RNA virus belonging to the Aphthovirus genus of the Picornaviridae family (1), which includes seven distinct serotypes (O, A, C, Asia-1, SAT-1, SAT-2, and SAT-3) and multiple subtypes worldwide (2). In Bangladesh, the FMDV type O Ind2001 lineage of the ME-SA topotype was reported to be homogenously distributed across the regions during 2011 and 2012 (3). …”
Section: Genome Announcementmentioning
confidence: 99%
“…FMDV Serotype "A" and "O" were consistently present in Bangladesh during 1996 to 2000 (Islam et al, 2000). The recent studies indicated that three different types (A, Asia-1 and O) were prevalent in Bangladesh during 2007 to 2008 (Sil and Taimur, 2000;Zinnah et al, 2010;Nandi et al, 2013). Serotype "O" was found to be responsible for 80% of the confirmed outbreaks, whereas "Asia 1" and "A" caused 12% and 8% outbreaks, respectively (Sarker et al, 2011;Hossen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%